The Spirituality of magis of St. Ignatius of Loyola in the configuration to christ (RFIS) in a theology seminary in the Philippines - Supremido, Joseph B. (Mary Help of Christians Theology Seminary : [s.n.], 2020)
This thesis-study aims to help the seminarians towards the configuration to Christ through the Spirituality of Magis of St. Ignatius of Loyola Configuration to Christ is a term that is coined in the document Ratio Fundamentalis Institutions Sacerdotale. The configuration Christ is also known the theology stage of priestly formation. Priestly fomation is integral meaning, the approach to human development is holistic. There are four pillars of priestly formation, namely, human, spiritual, intellectual, and pastoral.The Spirituality of Magis is a way of life in doing "more" for the greater glory of God. It verifies the importance of the exercise of human freedom as a means of cooperating to the grace freely offered by God. It does not refer on the quantity but of the quality of a person's response to becoming virtuous like Christ in all aspect of one's life. The novelty of the magis lies on being Christocentric which finds its highest expression in Christian discipleship through the patient endurance of a person's cross. This thesis-study aims to integrate the concept of magis in the different components of the four pillars of priestly formation. It endeavors to deepen the priestly formation by enabling and challenging the seminarians to respond well to the aforementioned formation. In essence, it challenges them, to undertake an unconditional and lifetime discipleship to Christ. The novelty of magis in the four pillars of the theology priestly formation is that it enhances the configuration to Christ.
Bibliography: pages 130-136.
CHED-La Union
Keywords: Catholic church -- Clergy -- Priest